Spontaneously Arising Canine Glioma as a Potential Model for Human Glioma. Issue 2 (February 2016) - Herranz, C.; Fernández, F.; Martín-Ibáñez, R.; Blasco, E.; Crespo, E.; De la Fuente, C.; Añor, S.; Rabanal, R.M.; Canals, J.M.; Pumarola, M.
Summary: Human gliomas are malignant brain tumours that carry a poor prognosis and are composed of a heterogeneous population of cells. There is a paucity of animal models available for study of these tumours and most have been created by genetic modification. Spontaneously arising canine gliomas may provide a model for the characterization of the human tumours. The present study shows that canine gliomas form a range of immunohistochemical patterns that are similar to those described for human gliomas. The in-vitro sphere assay was used to analyze the expansion and differentiation potential of glioma cells taken from the periphery and centre of canine tumours. Samples from the subventricular zone (SVZ) and contralateral parenchyma were used as positive and negative controls, respectively. The expansion potential for all of these samples was low and cells from only three cultures were expanded for six passages. These three cultures were derived from high-grade gliomas and the cells had been cryopreserved. Most of the cells obtained from the centre of the tumours formed spheres and were expanded, in contrast to samples taken from the periphery of the tumours. Spheres were also formed and expanded from two areas of apparently unaffected brain parenchyma. The neurogenic SVZ contralateral samples also contained progenitor proliferating cells, since all of them were expanded for three to five passages. Differentiation analysis showed that all cultured spheres were multipotential and able to differentiate towards both neurons and glial cells. Spontaneously arising canine gliomas might therefore constitute an animal model for further characterization of these tumours.